Statin-associated muscle disorders - Alan Xu; Vidya Limaye (Indian Journal of Rheumatology)
Statins are one of the most widely used and reputable medications worldwide, with strong evidence of mitigating cardiovascular complications and with a generally favorable safety profile. Nevertheless, statins have commonly come under scrutiny, owing to their associations with muscle disorders. Statins are known to cause a range of effects on muscles, varying from mild self-limiting symptoms to detrimental muscular necrosis. In particular, there has been emerging evidence of statin-associated necrotizing autoimmune myositis related to the presence of anti-3-hydroxy-3-methylglutaryl coenzyme A reductase (HMGCR) autoantibodies. Patients often demonstrate proximal muscle weakness and hyperCKemia, and treatment guidelines are not robust owing to the rarity of the disease. Nevertheless, literature provides evidence for use of corticosteroids, and there are emerging data supporting the incorporation of immunomodulatory agents such as methotrexate, intravenous immunoglobulin, and rituximab. In performing this review, we searched databases in PubMed and EMBASE written in English and limited to the last two decades. Keywords used included “statin,” “myositis,” “autoimmune myopathy,” “anti-HMGCR,” and “necrotising.” Articles were selected by relevance to the topic, and articles pertaining to antisignal recognition particle myopathy and other forms of myositis were excluded.